PELATIHAN MANAJEMEN PEMBUANGAN SAMPAH DI SD BETHEL, SUNGAI UKOI,KECAMATAN SUNGAI TEBELIAN - Sirhi, Sirilus; Warkintin, Warkintin; U, Lirui (Jurnal Pengabdian Masyarakat Khatulistiwa, 2023)
ABSTRACTSintang Regency is one of the eastern regions in West Kalimantan Province which is crossed by the Equator line located between 1o05' North Latitude and 0o46' South Latitude and 110o50' East Longitude and 113o20' East Longitude. This district has an area of 21,635 km². Sungai Ukoi Village is located in Sungai Tebelian sub-district. Residents of Sangai Ukoi Village, one part of 24 villages located in the capital of Sungai Tebelian Sub-district, Sungai Tebelian Sub-district, Sintang Regency which is located on the edge of Jalan Sintang Pontianak.Garbage is the remains of daily human activities and natural processes in solid form consisting of household waste. Waste consists of several types, namely organic, inorganic and toxic. Apart from waste sources, there are various types, including household waste, school waste, agricultural waste and building waste. Therefore, it is necessary to manage waste in our environment. Waste management is all activities carried out to handle waste from the time it is generated to final disposal. In general, waste management activities include controlling waste generation, waste collection, transfer and transport, processing and final disposal.Keywords: management, waste disposal ABSTRAKKabupaten Sintang merupakan salah satu daerah bagian Timur di Provinsi Kalimantan Barat yang dilalui oleh garis Khatulistiwa  terletak di antara 1o05’ Lintang Utara dan 0o46’ Lintang Selatan serta 110o50’ Bujur Timur dan 113o20’ Bujur Timur. Kabupaten ini memiliki luas wilayah 21.635 km². Desa Sungai Ukoi terletak di kecamatan Sungai Tebelian Penduduk Desa Sangai Ukoi, satu bagian dari 24 Desa yang berada di  Ibu Kota Kecamatan Sungai Tebelian, Kecamatan Sungai Tebelian Kabupaten Sintang yang terletak di Pinggir Jalan Sintang Pontianak.Sampah adalah sisa kegiatan sehari-hari manusia dan proses alam yang berbentuk padat yang terdiri atas sampah rumah tangga. Sampah terdiri dari beberapa jenis yaitu organik , anorganik dan beracun.selain  Sumber Sampah ada berbagai jenis ada yang dari sampah rumah tangga, sampah di sekolah, sampah pertanian dan sampah sisa bangunan. Oleh karena itu perlu nya pengelolaan sampah di lingkungan kita. Pengelolaan sampah adalah semua kegiatan yang dilakukan untuk menangani sampah sejak ditimbulkan sampai dengan pembuangan akhir. Secara garis besar, kegiatan pengelolaan sampah meliputi pengendalian timbulan sampah, pengumpulan sampah, transfer dan transpor, pengolahan dan pembuangan akhir.Kata Kunci : manajemen, pembuangan sampah